Fighting to keep the fire going: examining the relationship between public service motivation and burnout in singaporean public servants - Tan, Mavis (2017)
Public Service Motivation (PSM), an important resource of motivation in the public service, may lead to high turnover rates if left unmanaged, despite the need to retain passionate individuals. This paper thus examines if a relationship exists between PSM and burnout, specifically in Singapore’s public service, and if so, whether it is negative or positive, and if there are mediating or moderating effects from demographic and other motivation factors. Using surveys and follow-up interviews with individual public servants, this paper found that PSM is generally negatively correlated with burnout. Singapore public service employees also generally have high PSM but have either high or low burnout. These groups’ PSM and burnout are moderated by different demographic factors, and mediated by the perceived unsupportiveness of their environment. The paper recommends how to better manage the environment around public servants to reduce burnout levels and thus better utilize PSM as an invaluable resource.